"Caracterización de la almendra de cacao (Theobroma cacao L.) de 41 cruces internacionales en la finca experimental la represa" - Álvarez Escaleras, Malena Gissela (2018)
The present investigation was executed in the Experimental Farm "La Represa", located in the Fayta enclosure of the Quevedo - San Carlos road, province of Los Ríos, with a duration of 114 days. The cocoa almond (Theobroma cacao L.) of 41 interclonal crosses was characterized, using a completely randomized design (DCA), with 40 treatments, plus a control JHVH-10, with three repetitions and each experimental unit was composed of 20 fruits physiologically mature. To establish the differences between means, the Tukey test (p≤0.05) and (p<0.01) were applied. The best values registered for the physical characteristics: in seed index (IS) was, the T16 (DICYT-H-287) (1.79); number of almonds in 100 g, percentage of seed coat (PT), T23 (DICYT-H-294) (91), (20.88); Index of ear (IM), length of almond, T1 (DICYT-H-272) (24.11), (2.58 cm); almond width, the T29 (DICYT-H-300) (1.50cm). For fermentation: optimum T3 (DICYT-H-274) (44.00); median, T28 (DICYT-H-299) (59.67); almonds slate, T12 (DICYT-H-283) (15.00) and mold T4 (DICYT-H-275) (9.33). With respect to the chemical analysis, related to the paste: in humidity the T36 (DICYT-H-307) (0.99%), and minerals such as phosphorus, copper, iron, and zinc: (97.36 mg/100g), (7.70 mg/100g), (12.65 mg/100g) and (5.10 mg/100g); dry matter, ash, fat and energy the T28 (DICYT-H-299) (99.89%), (4.03%), (47.84%) and (623.08 kcal/100g); protein, T22 (DICYT-H-293) (28.31%) and T6 carbohydrates (DICYT-H-277) (46.49%); in; potassium, calcium and magnesium, T20 (DICYT-H-291) (183.75 mg/100g), (58.75 mg/100g) and (73.88 mg/100g). According to the sensory evaluation, for cocoa flavor the T11, T13 and T23 with (10); taste up T3, T4, T6, T10, T11 and T13con (10); fruit the T14, T9 and T24 with (9); candy T14 and T19 with (8). Keywords: cocoa, fermentation, sensory evaluation, pasta, minerals.